If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 + -3x = -1 Reorder the terms: 5 + 2x + -3x = -1 Combine like terms: 2x + -3x = -1x 5 + -1x = -1 Solving 5 + -1x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = -1 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = -1 + -5 -1x = -1 + -5 Combine like terms: -1 + -5 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| X=-0.9 | | 6.1=-3.5+6v | | 72=-1.33x | | 72=-1.33 | | 3(5x-3)+2(14-2x)-2(5x+2)=-1 | | 8-(-3x)=x | | 11=5y+-3y | | -1.1-(-10.1)= | | (6y+8)-(3+5y)=8 | | 400x= | | 15+h=10 | | 3(8)=n(0.08)(300) | | 8x+4=x-14 | | 13x^3-36x=-12x^2 | | 2x-3xm-3x*4=-2m-8 | | 4x-5x-3=0 | | 2x+8y=x-2y | | Y=-5/3-5 | | 2x--2=2 | | 3.4=15.9-5w | | 5x^2+3x=2x(x+6) | | 6p+6=5p+14 | | z+0.9=3.1 | | x(2-12-3m)=-8-2m | | r(1.4+35)=436.60 | | 4x-7=59-7x | | x-1/4=5 | | 2xc+-1c^2x+x=-10+5c | | 4x-3-4=24 | | x+2cx-c^2x=-10+5c | | X^2-25-144=0 | | (6*6-3*3*3)/7 |